Assistance for the Processing of Tofu Waste into Liquid Organic Fertilizer for Farmers in Sumberrejo District, Bojonegoro - Burhanuddin, Hamam; Manshur, Ahmad; Robbani, Shofa; Farhatin, Ummu (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This assistance was carried out in Sumuragung Bojonegoro District, part of the community who work as farmers and tofu production, in 2019 there were around 50 home industry units. Most manufacturers produce separately. Tofu craftsmen in the Sumuragung area pay little attention to the disposal of their processed waste because the production method is simple. Tofu production waste includes solid waste and liquid waste. Solid waste or what is usually called okara is often used as animal feed, while liquid waste resulting from the tofu making process is directly thrown into the drain without being processed first. Processed liquid waste has the potential to pollute the environment because it still contains protein and carbohydrate compounds which can ferment and cause an unpleasant odor. The result of this assistance is making POC from tofu waste so that people are more productive